Efeitos da administração de fentanil na concentração anestésica mínima e nas variáveis cardiorrespiratórias de galinhas (Gallus gallus domesticus) anestesiadas com isofluorano - Rocha, Rozana Wendler da [UNESP] (2016)
The aim of this study was to evaluate the effect of fentanyl on the isoflurane MAC over time and to evaluate the cardiorespiratory effects caused by this association in chickens. The individual isoflurane MAC of seventeen chickens was previously determined using the bracketing method. Hens were anesthetized with isoflurane under controlled ventilation to evaluate the effects of intravenous administration of 10 or 30 μg kg-1 of fentanyl over isoflurane MAC. In the next stage, cardiorespiratory effects of intravenous administration of 30 μg kg-1 of fentanyl were evaluated in seven chickens anesthetized with isoflurane under spontaneous ventilation through up-and-down method. Reduction of MAC was determined using logistic regression in each time interval and the 95 % Wald confidence interval was calculated. Data from physiological variables was analyzed using the Shapiro-Wilk test and RM one way ANOVA followed by the Tukey’s test. Results were considered significant when p < 0.05. At five and 15 minutes after administration of 10 μg kg-1 IV of fentanyl, isoflurane MAC was reduced by 18 % (6.1 to 29.1) e 6 % (-0.6 to 12.9), respectively. Administration of 30 μg kg-1 IV of fentanyl reduced isoflurane MAC by 43 % (13.3 to 71.9) e 13 % (-0.9 to 27.3) at five and 15 minutes, respectively. Cardiorespiratory data of birds anesthetized with isoflurane alone or associated with fentanyl did not differ. Fentanyl reduced dose-dependent the isoflurane MAC after 5 minutes of administration and did not cause significant cardiorespiratory depression in chickens anesthetized under spontaneous ventilation. Its applicability in clinical practice becomes limited since the duration of effect was short.